Character Education through Positive Habitation in the School - Wilianda Munthe; Mahidin Mahidin; Fitri Musliha; Tri Fatimah; Titi Nuraini, S (Universitas Muhammadiyah Enrekang, 2022)
Aek Hitetoras Village is one of the villages in the Marbau District, North Labuhanbatu Regency. This village is geographically located within the Marbau Subdistrict, Labuhan Batu Utara Regency, North Sumatra Province which is bordered by the north by Aek Kuo Subdistrict, to the east by Bilah Hulu Village, to the south by Bulungihit Village, to the west by PT. Smart TBK. The University as the organizer of the Tri-Dharma of Higher Education, especially the Real Work Class (KKN) synergizes in developing the region. With this KKN program, it will significantly encourage a dignified community specifically in education programs. With a participatory method in which the target of the implementation of KKN is the village community and residents of the Aek Hitetoras village school. In carrying out KKN 139 UINSU activities, students focus on the field of character education. Where is the target for UINSU 139 KKN participants in the field of education, participants go to local schools/madrasas? including 3 PAUD, 4 SD/MI, 1 MTs and 1 MA. other educational activities as well as holding children's competitions, in order to accommodate children's potential and develop children's creativity. The results of the study show that the education planting program character through positive habituation runs smoothly but it is not possible of course there are a few obstacles to be faced.